2020
DOI: 10.1111/dth.13539
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral facial edema after filler injection of the lower eyelid

Abstract: The use of hyaluronic acid (HA) gel fillers for rejuvenation of the face has been increasing in popularity over the years. This nonsurgical, temporary technique is commonly used in the periocular region to restore volume. The aim of this study was creating awareness in the potential causes of edema after hyaluronic acid gel filler injections under the eyes. A 32‐year‐old woman presented for a cosmetic consultation to address unilateral swelling of the left check. She states she had an HA filler injected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The time of onset of delayed complications in our study ranged from 2 weeks to 9 years. 8,12 We categorized the primary concerns and reported the mean onset time for each complication. However, this data may not be accurate due to heterogeneity in reporting between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time of onset of delayed complications in our study ranged from 2 weeks to 9 years. 8,12 We categorized the primary concerns and reported the mean onset time for each complication. However, this data may not be accurate due to heterogeneity in reporting between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that reported on volume of initial injection (n ¼ 11), an average of 1.2 mL was used total, or 0.6 mL per side. 7,[9][10][11][12] Complications A summary of the complications are depicted in ►Figure 5. The most common delayed complication following dermal filler treatment with any dermal filler was swelling (42.3%, 22/52) followed by lumps or nodules (25.0%, 13/52).…”
Section: Demographicsmentioning
confidence: 99%
“…Although IDFs are usually considered safe, the risk of complications is present; these latter can result as early-or late-onset incidents, and they include granulomas, nodules, material migration, and chronic cellulitis [5][6][7]. For many authors, homogeneous semipermanent or permanent fillers have been associated with many delayed cases of abscesses and granulomas [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…T he 21st century has gradually entered the era of minimally invasive treatment and minimally invasive plastic surgery, facial injection is one of the most important techniques of minimally invasive plastic surgery. 1 With the development of technology and the pursuit of beauty, people's acceptance of facial injections is also increasing. By injecting the filling material directly into the local or specific part, the effect of improving the physical and mental state is finally achieved.…”
mentioning
confidence: 99%
“…The causes of eye blinding complications during facial injection are as follows: (1) the filler accidentally enters the blood vessel; (2) excessive dosage of filler causes local tissue edema to compress blood vessels; (3) the syringe needle pierces the blood vessel wall and initiates the endogenous blood coagulation pathway; (4) local hemorrhage, hematoma, and adjacent tissues compress blood vessels. 6 The injured vessels are mainly the ophthalmic artery and its branches.…”
mentioning
confidence: 99%